Modelo de processo avaliativo na administração pública: um estudo de caso - Barcelos, Vinícius Adalberto de Souza (2001)
The mean goal of this work is to show the importance of the evaluation process to the development of the working process and results of brazilian's public administration. Actually, evaluation is something really important on public management, because it needs better products and services to solve social demands. In order to reach this goal, this work begins with a study about the actual context of brazilian - s public administration and how the figure of evaluation starts to get form and presence in each momento Toward this description, it will be built a model of an evaluation process for public administration, and be shown, step by step, the itens responsible to build this mode!. A govermental program will be analysed with the purpose to detect the run of the evaluation mode!. In this case, it will be studied the High Risk Pregnancy Program, developed by the Healthy Ministery. Evaluation will be analysed by the intersection of the concepts of the Organizations Theory with the Govermental Projects and Programs Evaluation.